Plant pharmacology: Insights into in-planta kinetic and dynamic processes of xenobiotics. Issue 19 (2nd October 2022) - Malchi, Tomer; Eyal, Sara; Czosnek, Henryk; Shenker, Moshe; Chefetz, Benny
Abstract: The exposure of plants to pharmaceuticals via treated wastewater irrigation and biosolid application presents an important route of chronic exposure of crops to a wide variety of bioactive pollutants. This paper presents a novel approach which aims to improve our understanding of the interactions of bioactive pollutants with plants through the concept of plant pharmacology and two main sub-divisions: (i) plant pharmacokinetics which describes the fate of exogenous xenobiotics in the plant based on the processes of absorption, distribution, metabolism and accumulation (ADMA), processes that are analogous to pharmacokinetics in animals; and (ii) plant pharmacodynamics that proposes that exogenous xenobiotics interact with plant enzymes and biochemical pathways, establishing a relationship with pharmacological concepts and emphasizing the importance of exposure-response interactions. The concept of plant pharmacology and its two subdivisions provide a foundation for the development of in-depth knowledge regarding the fate of xenobiotics in plants and establishing plant pharmacokinetic-pharmacodynamic models that include both the ADMA processes and time-dependent response of the plant to these compounds. This concept provides a new perspective on pharmacovigilance, focusing on plant-xenobiotic compound interactions, and a conceptual framework for understanding the fate and interactions of these bioactive molecules in agricultural systems, to enable more accurate risks assessments of environmental and human health. Graphical abstract: UF0001